Analisis Performansi Jaringan 4G LTE Dengan Metode Drive Test Pada Gedung Tokong Nanas Telkom University - Hamim Maafifa Nugraha; Rd. Rohmat Saedudin; Muhammad Fathinuddin (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The telecommunication system that is currently developing rapidly al-lows the public to enjoy a variety of communication and information technology telecommunication services in the form of the 4G LTE (Long Term Evolution) system. The 4G LTE network offers higher qual-ity services and high data transmission speeds. An online presence in the business environment, campuses, schools and other institutions is ur-gently needed considering that this information technology has made it easier to support communication processes and infrastructure that can be implemented. This study aims to analyze the 4G LTE network at the  using the drive test method. This method is a method of collecting data directly in the field to find out the actual conditions experienced by network users using certain devices. The data obtained during the drive test is in the form of 4G LTE signal strength parameters, namely RSRP (Reference Signal Received Power), RSRQ (Received Signal Reference Quality) and SNR (Signal to Noise Ratio). Based on the research results, it can be concluded that the signal strength on the RSRP parameter with a signal range above -90 dBm is on the 4th floor with a percentage of 87.17% in a good category. Meanwhile, the RSRQ parameter with a signal range above -7 dB is on the 3rd floor with a percentage of 1.11% in a good category and the SNR parameter with a signal range above 11 dB is on the 3rd floor with a percentage of 11.11% in a good category.